The Application of Response Surface Methodology (RSM) on the Optimization of Catfish Bone Calcium Extraction - Susana Endah Ratnawati; Nurfitri Ekantari; Rizky Wana Pradipta; B L Paramita (Jurnal Perikanan Universitas Gadjah Mada, 2018)
This study was designed to determine the optimum conditions on catfish bone calcium extraction through Response Surface Methodology (RSM) which used factorial design and 13 treatments. Tests were used to know the influence of independent variables (solvents concentrations and treatment time) on the calcium content of bone flour. As a result, linear models were used as response prediction. Maximum response was obtained by calcium extraction using 5% NaOH during 30 minutes or 11.64% HCl within 58 minutes. It is shown that calcium content were 15.74-17.46% with more than 87.5% accuracy level. Calcium extraction using 5% NaOH during 30 minutes produced flour which has Ca/P ratio 3:1, maximum yield and whiteness level. Low protein and moisture content might result in the long shelf life of catfish bone flour.